ETYMOLOGICAL CHARACTERISTICS OF AGRICULTURAL TERMINOLOGY IN UZBEK AND ENGLISH - Qodirova Gulbahor Turdiyevna (Western European Studies, 2025)
This article investigates the etymological characteristics of agricultural terminology in Uzbek and English, focusing on their historical development, lexical layers, and cultural influences. The study identifies the core native vocabulary in each language – Germanic in English and Turkic in Uzbek–along with successive layers introduced through contact with prestige languages: Norman French and Latin/Greek in English; Persian, Arabic, and later Russian/European in Uzbek. The analysis reveals that both languages demonstrate a stratified lexical structure where older layers encompass basic farming concepts, while later borrowings introduce specialized and technical terms. Comparative analysis highlights shared sociolinguistic patterns in terminology formation, modernization strategies, and cultural emphases, as well as key differences in lexical replacement and preservation. The findings contribute to cross-linguistic studies in etymology, historical linguistics, and agricultural terminology standardization
Keywords: agricultural terminology; etymology; English